A comparative study of the effectivity of MSC-based, NP-based and combined therapies in an experimental model of NaIO3-induced retinal degeneration - Palacka, Katerina; Hermankova, Barbora; Cervena, Tereza; Rossner, Pavel; Holan, Vladimir; Javorkova, Eliska (Scientific reports, 2025)
Mesenchymal stem cells (MSCs) represent the promising options for retinal therapy and combined therapy with nanoparticles (NPs) could currently provide increased immunoregulatory and neuroprotective effects. Therefore, we tested the effect of silver (Ag)NPs on the properties of MSCs in an experimental model of chronic retinal degeneration. The results showed that simultaneous administration had no effect on the survival of MSCs, but a less effective local regulation of Iba-1 expression compared to MSC- or AgNP-only treated groups was observed. In addition, MSCs applied alone or in combination with AgNPs and sorted from the degenerated retina had increased expression of genes for retinal markers (rhodopsin, S-antigen, recoverin), and for TGF-β and IGF-1. These effects were confirmed also on protein level by increased production of IGF-1 and proportion of rhodopsin+ MSCs. Nevertheless, the increased expression of the gene for GDNF was observed only in the MSCs combined with AgNPs. Regarding the immune response, the application of MSCs with AgNPs triggered increased expression of the IL-6 gene in the CD45 cells separated from the retina. In conclusion, applications of MSCs or AgNPs, as a single therapy, were able to modulate the inflammation. However, the combined applications decreased the immunomodulatory effects of MSCs or AgNPs.
Keywords: Animals; kovové nanočástice; mezenchymální kmenové buňky; kombinovaná terapie; Retina; Silver; Mice; Iodates; Metal Nanoparticles; degenerace retiny; transplantace mezenchymálních kmenových buněk; myši; jodičnany; Mesenchymal Stem Cells; Silver nanoparticles; Mesenchymal Stem Cell Transplantation; modely nemocí na zvířatech; Combined Modality Therapy; Mesenchymal stem cells; Disease Models, Animal; retina; zvířata; Retinal Degeneration; stříbro; Retinal microglia